(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article examines the expression of personal aspects of a writer through the biographical method. It highlights the skill of writers in using the biographical method, and also substantiates the presence of information in works regarding the biography of the writer using this method.